Measuring skill and chance in games - Dürsch, Peter; Lambrecht, Marco; Oechssler, Joerg (European economic review, 2020)
Online and offline gaming has become a multi-billion dollar industry, yet, games of chance (in contrast to games of skill) are prohibited or tightly regulated in many jurisdictions. Thus, the question whether a game predominantly depends on skill or chance has important legal and regulatory implications. In this paper, we suggest a new empirical criterion for distinguishing games of skill from games of chance. All players are ranked according to a “best-fit” Elo algorithm. The wider the distribution of player ratings are in a game, the more important is the role of skill. Most importantly, we provide a new benchmark (“50%-chess”) that allows to decide whether games predominantly depend on chance, as this criterion is often used by courts. We apply the method to large datasets of various games (e.g. chess, poker, backgammon). Our findings indicate that most popular online games, including poker, are below the threshold of 50% skill and thus depend predominantly on chance. In fact, poker contains about as much skill as chess when 75% of the chess results are replaced by a coin flip.
Gesehen am 24.08.2020